Multilayer Model of Pharmacy Participation in the Antimicrobial Stewardship Program at a Large Academic Medical Center. Issue 9 (October 2017) - Dubrovskaya, Yanina; Scipione, Marco R.; Siegfried, Justin; Jen, Shin-Pung; Pham, Vinh; Papadopoulos, John; Decano, Arnold; Lewis, Tyler; Dabestani, Arash
Purpose: Leveraging pharmacy personnel resources for the purpose of antimicrobial stewardship program (ASP) operations presents a challenging task. We describe our experience integrating all pharmacists into an ASP, and evaluate the impact on ASP interventions, antimicrobial utilization, rate of selected hospital-onset infections and readmission.Summary: During a study period (January 1 to December 31, 2015), a total of 14 552 ASP-related pharmacy interventions were performed (ASP clinical pharmacotherapy specialists [CPS] n = 4025; non-ASP CPS n = 4888; hospital pharmacists n = 5639). Sixty percent of interventions by ASP CPS were initiated utilizing the dedicated ASP phone, and 40% through prospective audit and feedback. Non-ASP CPS performed interventions during bedside rounds (dose adjustment 23%, initiate new or alternative anti-infective 21%, discontinue antibiotic(s) 12%, therapeutic drug monitoring 11%, de-escalation 4%), whereas hospital pharmacists participated at the point of verification (dose adjustment 75%, restricted antibiotic verification 15%, and reporting major drug-drug interactions 4%). The acceptance rate of interventions by providers and clinicians was >90% for all groups. Annual aggregate antimicrobial use decreased by 6.4 days of therapy/1000 patient-days (DOT/1000 PD; P = 1.0). Ceftriaxone use increased by 8.4 DOT/1000 PD ( P = .029) without a significant compensatory increase in the use of antipseudomonal agents. Sustained low rates of hospital-onset Clostridium difficile (CDI) and carbapenem-resistant Enterobacteriaceae (CRE) infections were observed in 2015 compared with the prior year (1.1 and 1.2 cases/1000 PD, 0.2 and 0.1 cases/1000 PD, respectively). Thirty-day readmission rate decreased by 0.6% ( P = .019).Conclusions: Integration of all pharmacists into ASP activities based on the level of patient care and responsibilities is an effective strategy to expand clinical services provided by ASP.